Paso por aqui' - Rhodes, Eugene Manlove; Hutchinson, W. H.; Koerner, W. H. D. (University of Oklahoma Press Norman, Oklahoma, 1926)
Tales of the old west.
Keywords: Frontier and pioneer life -- West (U.S.) -- fiction